Rare Perilunate Injury as a Result of Chronic Trauma in 3-Year-Old Girl - Tomaszewski, Ryszard (European Journal of Pediatric Surgery Reports, 2015)
A 3-year-old girl was reported to have perilunate dislocation. The child had suffered, approximately 18 months before, a repetitive wrist injury by means of frequent pulling and bending of the hand by the father who may have physically abused the child for approximately 2 months. At the age of 3 years and 4 months, we performed the reduction of the perilunate dislocation and the plasty of the dorsal scapholunate ligament using the capsular flap prepared from the extensor retinaculum. The wrist was immobilized for 6 weeks. Two months after surgery, patient started the physiotherapy for 3 months. The patient could flex up the wrist to 40 degrees and extend up to 45 degrees (mobility of the healthy wrist was 60, 50 degrees) during the examination 24 months' post-op. Only the surgical treatment of the perilunate dislocation can lead to obtain the good surgical result.
Keywords: child perilunate dislocation; chronic trauma; wrist child injury